ICT Innovations 2016 Cognitive Functions and Next Generation ICT Systems - Stojanov, Georgi; Kulakov, Andrea (Advances in Intelligent Systems and Computing,, 2018)
The International Conference on ICT Innovations was held in September 2016, in Ohrid, Macedonia, with the main topic "Cognitive Functions and Next Generation ICT Systems". We live in the era where technologies are intimately woven into virtually all aspects of daily life and are becoming almost invisible. While these technologies have considerable benefits, they also have a number of shortcomings and unforeseen consequences. For example, on the one hand, bodily sensors that track physical activity, physiological parameters and sleep patterns can help promote healthy habits and can enable early detection of problems. On the other hand, attention spans are becoming shorter and shorter due to constant interruptions by notifications, emails, and instant messages being delivered to cell phones or watches, and similar disturbances. Moreover, the privacy issues involved in storing and manipulation of these data must not be neglected. The technological convergence of sciences that were considered separate in the past, like information and communication technologies, cognitive sciences, nanotechnologies and biotechnologies, determines not only our society, health and economy, but also our education and culture. The conference gathered academics, professionals and practitioners involved in developing solutions and systems in the industrial and business arena, especially innovative commercial implementations, to discuss novel applications of these next-generation, emerging technologies in the context of human cognitive functions.